Application of the rules of international humanitarian laws to Palestinian prisoner in Israel - Salman, Hamza Ahmed Khalil (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2020)
With the beginning of the Israeli occupation of Palestine, several forms of Palestinian resistance erupted to confront this occupation, resulting in the capture of many Palestinians, where the Israeli occupation has carried out systematic policies on detainees to destroy the will of the Palestinian people to achieve their freedom and self-determination. This has made the issue of prisoners one of the most important issues that Palestinians suffer in their daily lives. Therefore, this study aimed to clarify the role of international humanitarian law in protecting prisoners, the rights granted to prisoners by international treaties and conventions, and the Israel's application of the rules of international humanitarian law to Palestinian prisoners and implications of non - compliance with the international law to the Palestinians in Israel prisons. The research is based on doctrinal and qualitative methods, which use the sources of international humanitarian law in relation to prisoners' rights, which is one of the branches of international law. The study highlights the rights of Palestinian prisoners and psychological, physical and legal violations committed against them in Israeli prisons, the possible legal mechanisms in defend their rights. The study dealt with the history of the Palestinian-Israeli conflict. It also provides a general classification of prisoners of war and who were entitled to describe prisoners of war and the rights granted to them in accordance with the Third and Fourth Geneva Conventions and its protocols. also discusses the violations committed by the Israeli occupation against Palestinian prisoners, which are the inhuman treatment they are subjected to, and the passage of a group of laws that violate rights of Palestinian prisoners. As well as, the possible legal mechanisms in defending the issue of Palestinian prisoners, both at local level by activating the diplomatic, legal and media role in supporting the issue of Palestinian prisoners, and activate the role of official and informal local institutions and at international level by activating the role of the Security Council in the implementation of the rules of international law and human rights bodies. In view of Israel's claim of application international humanitarian law and its ratification of the Geneva Convention, the study concluded that Israel denies Palestinian of rights as prisoners of war, describes them as illegal combatants and claims that the Convention does not apply to the occupied Palestinian territories, although international humanitarian law under the Geneva Convention includes members of the resistance and organized armed forces. therefore, Palestinian prisoners are considered prisoners of war.